Педагогічні умови формування досвіду спільної діяльності у дітей передшкільного віку засобами художньої праці - Венгер, Алла Олександрівна (My University, 2024)
Наукова робота присвячена аналізу такого аспекту проблеми соціалізації дітей передшкільного віку, як формування в них навичок спільної діяльності. Проаналізовано основні наукові розробки з проблеми феноменології спільної діяльності, її зв’язку із взаємодією та колективною діяльністю. Вказано на специфіку набуття дітьми передшкільного віку досвіду спільної діяльності. Розкрито потенціал художньої праці щодо забезпечення соціалізуючих засад спільної діяльності дітей передшкільного віку. Здійснено діагностику сформованості досвіду спільної діяльності дошкільників у процедурі проведення констатувального експерименту. Розроблено критерії і показники, виявлено та обґрунтовано рівні сформованості досвіду спільної діяльності в дітей передшкільного віку засобами художньої праці. Визначено педагогічні умови формування досвіду спільної діяльності дітей передшкільного віку засобами художньої праці та розроблено методичні матеріали щодо забезпечення кожної із цих умов.
joint activity in preschool children by means of artistic work. Qualification work. Nizhyn, 2024. 106 p. – in Ukrainion. The scientific work is devoted to the analysis of such an aspect of the problem of socialization of preschool children as the formation of their skills of joint activity. The main scientific developments on the problem of the phenomenology of joint activity, its connection with mutual and collective activity are analyzed. The specifics of the acquisition of joint activity experience by preschool children are indicated. The potential of artistic work is revealed in terms of ensuring the socializing potential of joint activity in preschool children. Diagnostics of the formation of the experience of joint activity of preschoolers in the procedure of conducting a ascertaining experiment is carried out. Criteria and indicators are developed, the levels of formation of the experience of joint activity in preschool children by means of artistic work are identified and substantiated. The pedagogical conditions for the formation of the experience of joint activity of preschool children through artistic work have been determined and methodological materials have been developed to ensure each of these conditions. Keywords: joint activity, interaction, collective activity, experience, experience of activity, experience of joint activity, artistic work, preschool children.
Keywords: спільна діяльність; взаємодія; колективна діяльність; досвід; досвід спільної дільності; художня праця; діти передшкільного віку